2020
DOI: 10.1136/annrheumdis-2020-218846
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on ‘Ultrasound shows rapid reduction of crystal depositions during a treat-to-target approach in gout patients: 12-month results from the NOR-Gout study’

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting, or dissemination plans of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Hung et al comment on the lack of control group in our study, and they suggest a double-blind, controlled study to explore the effectiveness of ULT, and they comment on the lack of information regarding blindness of operators and participants. 1 We certainly agree on a randomised controlled trial (RCT) being necessary to confirm our findings, which are based on an observational study without a control group, where neither sonographers nor patients were blind to the treatment. However, since in addition to our study, several smaller studies have shown the reduction of urate depositions during ULT, [2][3][4][5][6] and given the strong recommendations to reduce serum urate levels in gout to a target, 7 8 a long-lasting RCT with a control group not treated according to current guidelines, at least in Scandinavia, seems not ethically acceptable to patients.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Hung et al comment on the lack of control group in our study, and they suggest a double-blind, controlled study to explore the effectiveness of ULT, and they comment on the lack of information regarding blindness of operators and participants. 1 We certainly agree on a randomised controlled trial (RCT) being necessary to confirm our findings, which are based on an observational study without a control group, where neither sonographers nor patients were blind to the treatment. However, since in addition to our study, several smaller studies have shown the reduction of urate depositions during ULT, [2][3][4][5][6] and given the strong recommendations to reduce serum urate levels in gout to a target, 7 8 a long-lasting RCT with a control group not treated according to current guidelines, at least in Scandinavia, seems not ethically acceptable to patients.…”
supporting
confidence: 63%
“…Response to: 'Correspondence on 'Ultrasound shows rapid reduction of crystal depositions during a treat-to-target approach in gout patients: 12-month results from the NOR-Gout study'' by Hung et al We appreciate the interest by Hung et al 1 in our article describing the rapid reduction of ultrasound-detected crystal depositions in gout during 12 months of treat-to-target follow-up on uratelowering treatment (ULT).…”
mentioning
confidence: 99%